The complete chloroplast genome sequence of Epipremnum aureum and its comparative analysis among eight Araceae species - Na Tian; Limin Han; Chen Chen; Zhezhi Wang (2018)
Epipremnum aureum is an important foliage plant in the Araceae family. In this study, we have sequenced the complete chloroplast genome of E. aureum by using Illumina Hiseq sequencing platforms. This genome is a double-stranded circular DNA sequence of 164,831 bp that contains 35.8% GC. The two inverted repeats (IRa and IRb; 26,606 bp) are spaced by a small single-copy region (22,868 bp) and a large single-copy region (88,751 bp). The chloroplast genome has 131 (113 unique) functional genes, including 86 (79 unique) protein-coding genes, 37 (30 unique) tRNA genes, and eight (four unique) rRNA genes. Tandem repeats comprise the majority of the 43 long repetitive sequences. In addition, 111 simple sequence repeats are present, with mononucleotides being the most common type and di- and tetranucleotides being infrequent events. Positive selection pressure on rps12 in the E. aureum chloroplast has been demonstrated via synonymous and nonsynonymous substitution rates and selection pressure sites analyses. Ycf15 and infA are pseudogenes in this species. We constructed a Maximum Likelihood phylogenetic tree based on the complete chloroplast genomes of 38 species from 13 families. Those results strongly indicated that E. aureum is positioned as the sister of Colocasia esculenta within the Araceae family. This work may provide information for further study of the molecular phylogenetic relationships within Araceae, as well as molecular markers and breeding novel varieties by chloroplast genetic-transformation of E. aureum in particular.